Georgia's innovative policy and system - Abesadze, Ramaz (Ivane Javakhishvili Tbilisi State University Paata Gugushvili Institute of Economics, 2023)
The processes of innovative policy and innovative system formation in Georgia are investigated and the main directions of innovative policy of Georgia are defined.
1. Abesadze R. 2022 (1)The main directions the innovation strategy of the Georgia economy. “Ekonomisti” 2022 № 2 2. Abesadze R. 2022 (2). "Open innovation", "open science", national innovation system and its models. Collection of materials of the international scientific conference: "Innovative development of the economy: world experience and perspectives", Tbilisi 2021. 3. Абесадзе Р. 2016. Инновации, инновационные сети и общие направления формирования инновационной экономики в Грузии. XVII Международная научная конференция; „Предпринимательство, социальная организация в структурах сети. Опыт и перспективы развития в Центральной и Восточной Европе” (23-25 мая 2016 года, Польша) 4. Abesadze R. 2021. Economic Development and Economic Growth in Georgia at Modern Stage. "Bulletene" of the National Academy of Sciences of Georgia, 2021, № 4 5. Matias Braun, Sebastián Bustos, Luis Felipe Céspedes. 2021. Innovation Strategy and Economic Development. https://www.cgdev.org/sites/default/files/WP590-Innovation-strategy-economic-development.pdf 6. Business clusters. 2023 (in Georgian) https://www.gda.ge/shared/UserFiles/Images/UNIDO%20Cluster%20Presentation_GEO.pdf 7. Evaluation of the results of the industrial part, technical support and access to finance components of the “Produce in Georgia” program. 22018 (in Georgian) https://bit.ly/3k4brFM 8. Natural drink "kombucha" enterprise was opened in the village of Karafila. 2021 (in Georgian) https://bm.ge/ka/article/sofel-yarafilashi-naturaluri-sasmelis-kombuchas-sawarmo- gaixsna/92126 9. Results of the programs of the agency "Produce in Georgia". 2021 (in Georgian) https://www.enterprisegeorgia.gov.ge/ka/სიახლეები/სააგენტოს-აწარმოე- საქართველოში-18 10. Technoparks. 2023 (in Georgian)https://gita.gov.ge/regions 11. Turnava N. 2020. The new enterprise of "Kartli Textile" will employ up to 4,000 people, 90 percent of whom are women. 2020 (in Georgian https://www.interpressnews.ge/ka/article/635641-natia-turnava-kartli-tekstilis-axali-sacarmo-4-000-mde-adamians-daasakmebs-romelta-90-procenti-kali
Keywords: innovative development, innovative policy, innovative system